The globalization of human rights - Coicaud, Jean-Marc.; Doyle, Michael, 1948-; Gardner, Anne-Marie. (Tokyo ; New York : United Nations University Press, 2003)
This work focuses on the imperatives of justice at the national, regional, and international levels through an analysis of civil, political, economic, and social rights.
Preliminaries; Contents; Introduction Human rights and international order; 1 On the relationships between civil and political rights, and social and economic rights; 2 The incorporation of civic and social rights in domestic law; 3 Comparative practice on human rights: North-South; 4 Human rights and Asian values; 5 The politics of human rights; 6 Global accountability; Conclusion Human rights in discourse and practice The quandary of international justice; Acronyms; Index.
"The product of a research project conducted under the auspices of the Peace and Governance Programme of the United Nations University"--Page vii
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Human rights; Civil rights; Political rights; Globalization; Human Rights; Droits de l'homme (Droit international); Droits politiques; Mondialisation; globalism; POLITICAL SCIENCE -- Political Freedom & Security -- Civil Rights; POLITICAL SCIENCE -- Political Freedom & Security -- Human Rights; Droits civils; Droits de l'homme.; Droits politiques; Mondialisation; Civil rights; Globalization; Human rights; Political rights; Menschenrecht; Mensenrechten; Internationalisatie; princeton <NJ, 1999>